Hubungan Asupan Makanan, Status Gizi, Lama Menjalani Kemoterapi dan Dukungan Keluarga dengan Kualitas Hidup Pasien Kanker Payudara (Studi di Rumah Sakit Umum Daerah Ulin Kota Banjarmasin) - Arisa Rizqiyah; Rijanti Abdurrachim (HB PRESS, 2022)
Background: Breast cancer certainly has a big impact on the sufferer, physically, psychologically, socially, spiritually and other aspects of life. This certainly affects the quality of life of breast cancer patients. Objective: To analyze the relationshipbetween food intake, nutritional status, duration of chemotherapy and family support with the quality of life of breast cancer patients at Ulin Hospital Banjarmasin. Methods: observational analytic using a cross sectional research design. The population was all breast cancer patients at Ulin Hospital Banjarmasin were 92 people based on data in December 2019. The sample was taken using a non-probability sampling technique based on inclusion and exclusion criteria as many as 48 people. Primary data were obtained through interviews and anthropometric measurements. Data analysis used Spearman Rank correlation test with 95% confidence level. Results: Energy intake deficit (70.9%), protein intake deficit (54.1%), fat intake deficit (68.8%), carbohydrate intake deficit (66.7%), nutritional status normal (47.9% ), chemotherapy 3 months (72.9%), good family support (91.7%) and moderate quality of life (75%). Conclusion: There is a relationship between food intake, nutritional status and duration of chemotherapy with the quality of life of breast cancer patients at Ulin Hospital Banjarmasin and there is no relationship between family support and quality of life of breast cancer patients at Ulin Hospital Banjarmasin. Suggestion: Nutritionists are expected to provide nutritional consultation regarding food intake for cancer patients, respondents are expected to increase food intake, and respondent’s families are expected to pay attention to the patient's diet and provide information support.